2021
DOI: 10.3389/fendo.2021.644159
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Hyperinsulinemia and Hyperglycemia in the Impaired Glucose Tolerance Stage Mediate Endothelial Dysfunction Through miR-21, PTEN/AKT/eNOS, and MARK/ET-1 Pathways

Abstract: BackgroundImpaired glucose tolerance (IGT) is an important prediabetic stage characterized by elevated concentrations of glucose and insulin in the blood. The pathological hyperglycemia and hyperinsulinemia in IGT may regulate the expression of microRNA-21 (miR-21) and affect the downstream insulin signaling pathways, leading to endothelial cell dysfunction and early renal damage.MethodsThe individual and combined effects of insulin and glucose were investigated using human glomerular endothelial cells (HGECs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…IR is also characterized by the impairment of endothelial function, and IR is inversely associated with median colony forming unit endothelial cells, causing the decreased density of collaterals in response to cardiac ischaemia [ 13 ]. A recent study revealed that IR could decrease the expression of MicroRNA-21, an important mediator that regulates the secretion of nitric oxide (NO) and endothelin-1, thereby causing endothelial dysfunction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…IR is also characterized by the impairment of endothelial function, and IR is inversely associated with median colony forming unit endothelial cells, causing the decreased density of collaterals in response to cardiac ischaemia [ 13 ]. A recent study revealed that IR could decrease the expression of MicroRNA-21, an important mediator that regulates the secretion of nitric oxide (NO) and endothelin-1, thereby causing endothelial dysfunction [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was performed to assess the expression levels of eNOS, Egr-1, and VEGF in hGECs [ 15 ]. Briefly, cellular lysates extracted from hGECs was separated by 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels, transferred onto polyvinylidene fluoride (PVDF) membranes, and incubated with primary antibodies and HRP-labeled secondary antibodies (eNOS: #32,027; Egr-1: #4154; GAPDH: # 5174; secondary antibodies #7074 and #7076, Cell Signaling Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Visceral obesity leads to endothelial dysfunction through the effects of resistin, interleukin (IL)-6 ( Aroor et al, 2013 ), and tumor necrosis factor α (TNF-α; Marincowitz et al, 2019 ) on eNOS phosphorylation. Dyslipidemia can lead to excessive FFAs in plasma ( Sekizkardes et al, 2020 ), thereby weakening PI3K/Akt pathway conduction, increasing reactive oxygen species (ROSs), and increasing endothelin-1 (ET-1) production, which together lead to endothelial dysfunction ( Liu et al, 2021 ; Figure 3D ).…”
Section: Relationship Between the Akt Pathway And Endothelial Dysfunc...mentioning
confidence: 99%